Interglacial analogues of the Holocene and its natural near future. (15th July 2015) - Yin, Qiuzhen; Berger, André
Abstract: In an attempt to find potential interglacial analogues of our present interglacial and its natural future, five interglacials (MIS-1, 5, 9, 11 and 19) are studied in terms of their astronomical characteristics, greenhouse gases concentration and climate simulated using both snapshot and transient experiments. Transient simulations covering a full range of obliquity, precession and eccentricity allow to develop an OPE index to estimate the climate sensitivity to astronomical forcing. They also show that obliquity and precession have different weight on the annual mean temperature and precipitation of different latitudinal zones, leading to varying phasing of these climate variables between different latitudes. However, the variations in boreal summer temperature of different latitudes (except the Southern Ocean) are in phase and are dominated by precession. All the interglacials are shown to be warmer than the natural climate of the present day and of the next centuries during boreal summer and for the annual mean temperature with varying duration and intensity. Such warming is mainly caused by changes in insolation, unlike the present global warming which mainly results from anthropogenic CO2 increase. The exceptionally long duration of MIS-11 is confirmed by our simulations, and it is demonstrated to be related to the long-lasting low eccentricity and high CO2 concentration and to the anti-phase relationship between obliquity maximum and precession minimum during MIS-11. As far as the variations of annual and seasonal temperatures are concerned, both snapshot and transient simulations show that MIS-19 is the best analogue of the present interglacial. MIS-11 is also a decent analogue when the impact of insolation alone is considered, but it is warmer than MIS-1 when the impact of CO2 is additionally included. Due to the large amplitude in the variations of insolation, MIS-5 and MIS-9 can hardly be considered as an analogue of the natural present-day climate and of its near future, but such warm climates could be, at least partly, considered as analogues of the future man-made warm climate. Although their astronomical forcing is different from the future and their CO2 concentration is much lower, the past interglacials have similarities to the anthropogenic warming in terms of climate feedbacks at the regional scale. Highlights: Five warm interglacials are intercompared with both snapshot and transient simulations. Relationships between astronomical parameters and temperature and precipitation of different latitudes are examined. Contributions of insolation and CO2 to the intensity and duration of the five interglacials are discussed. Analogue of the Holocene and its natural future is looked for from the past interglacials.